Nonyiane Sebagai Kawasan Lindung Tradisional Di Negeri Sepa, Kecamatan Amahai Kabupaten Maluku Tengah - Latuconsina, Nilam U; Badaruddin, Ernywati; Kaya, Manuel (Jurnal Agrosilvopasture-Tech, 2025)
This research aims to determine the process of handling the bodies of the Nuaulu Tribe as well as the impact of the Nuaulu Tribe Traditions in Sepa Country on the environment and to find out why the bodies of the Nuaulu Tribe do not emit an odor even though they are not buried. This research uses descriptive research methods with a qualitative approach. The research instrument generally carried out by researchers is field observation. The Nuaulu Tribe community in Sepa Village was used as a sample in the research. The results show that the Traditional process of handling the bodies of the Nuaulu tribe is a traditional ritual passed down from the ancestors where the deceased person is laid to rest in the funeral home, then wrapped in a mat, taken into the traditional house where the traditional head wil pray. The body of the deceased person is not put in the grave, but only placed on a para-para bamboo (a bamboo pole like a bed). The handling place for the Nuaulu Tribe (nyonyiane) is a forest dominated by bamboo plants and is a place that the Nuaulu Tribe community can enter and that is only for certain people from that tribe. The body was placed on a para-para covered with mats and Galoba (Hornstedtia alliacea) stems without any form of preservation.